2019
DOI: 10.3390/nano9020136
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Water Softening with TEMPO-Oxidized/Phosphorylated Nanopapers

Abstract: Water hardness not only constitutes a significant hazard for the functionality of water infrastructure but is also associated with health concerns. Commonly, water hardness is tackled with synthetic ion-exchange resins or membranes that have the drawbacks of requiring the awkward disposal of saturated materials and being based on fossil resources. In this work, we present a renewable nanopaper for the purpose of water softening prepared from phosphorylated TEMPO-oxidized cellulose nanofibrils (PT-CNF). Nanopap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The increase in the lateral size of the GO and also the increase in zeta potential value after the inclusion of the divalent ion in the GO suspension indicated that Mg 2+ and Ca 2+ showed good affinity towards the oxygen functional groups GO sheets are highly negative charged which is attributed to the ionization of oxygen-containing functional groups present at the basal and planar plane. We posit that the higher particle diameter obtained for rGH-Ca is attributed to the larger ionic size of Ca 2+ for easier chelation with the oxygenated group of the GO [48]. The higher hydration energy of MgCl 2 led to the greater volumetric dimension of its hydrated ion which may limit their interactions via ionic cross-linking with the negatively charged GO sheets [49].…”
Section: Characterization Of Go Colloidal Suspension In the Presence mentioning
confidence: 92%
“…The increase in the lateral size of the GO and also the increase in zeta potential value after the inclusion of the divalent ion in the GO suspension indicated that Mg 2+ and Ca 2+ showed good affinity towards the oxygen functional groups GO sheets are highly negative charged which is attributed to the ionization of oxygen-containing functional groups present at the basal and planar plane. We posit that the higher particle diameter obtained for rGH-Ca is attributed to the larger ionic size of Ca 2+ for easier chelation with the oxygenated group of the GO [48]. The higher hydration energy of MgCl 2 led to the greater volumetric dimension of its hydrated ion which may limit their interactions via ionic cross-linking with the negatively charged GO sheets [49].…”
Section: Characterization Of Go Colloidal Suspension In the Presence mentioning
confidence: 92%
“…Thin nanocellulose lms, also called nanopapers, show great potential in a myriad of possible applications such as substrates for printable electronics, (Koga et al 2013(Koga et al , 2014Fujisaki et al 2014;Zhu et al 2014) water treatment membranes, (Mautner et al 2015(Mautner et al , 2016(Mautner et al , 2019Mautner 2020;Fijoł et al 2023) and interleaves in composite reinforcements (Mautner et al 2017(Mautner et al , 2020) amongst many others. These applications pose different requirements on nanopapers, rendering the tuneability of the mechanical, optical and morphological properties a necessity.…”
Section: Introductionmentioning
confidence: 99%
“…Direct feed of hard water to the boiler reduces the steam production due to the presence of metal ions, which, forming scale and sludge, priming and foaming, can greatly reduce the heat transfer efficiency 1 . Moreover, the scale formation during industrial activities produces boiler corrosion and blokage of membranes and pipes 2 . Hence the necessity to soften the water prior to use in such applications.…”
Section: Introductionmentioning
confidence: 99%